2016
DOI: 10.1021/acscatal.5b02543
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Spectroscopic Study of CO2 Electroreduction at Copper Electrodes in Acetonitrile

Abstract: The electrochemical conversion of carbon dioxide (CO 2 ) into valuable compounds is a promising route toward the valorization of this molecule of high environmental impact. Yet, an industrial process involving CO 2 electroreduction is still far from reality and requires deep and fundamental studies for a further understanding and better development of the process. In this work, we describe in situ spectroelectrochemical studies based on Fourier transform infrared spectroscopy and surface-enhanced Raman spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
263
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(295 citation statements)
references
References 47 publications
(105 reference statements)
20
263
2
Order By: Relevance
“…In contrast, all samples with adsorbed CO 2 show absorption signals in two distinct infrared bands at room temperature in Supplementary Fig. 9c,d, that is, 2,380–2,300 cm −1 , which is associated with CO 2 molecules25 on the sample surface, and 1,500–1,430 cm −1 , which is typically observed for CO 3 2− (ref. 26).…”
Section: Resultsmentioning
confidence: 94%
“…In contrast, all samples with adsorbed CO 2 show absorption signals in two distinct infrared bands at room temperature in Supplementary Fig. 9c,d, that is, 2,380–2,300 cm −1 , which is associated with CO 2 molecules25 on the sample surface, and 1,500–1,430 cm −1 , which is typically observed for CO 3 2− (ref. 26).…”
Section: Resultsmentioning
confidence: 94%
“…We note that the reported gas-phase and liquid-phase spectra of PO show bands in the 1000-1500 cm À 1 range, [18] but these bands are too weak (see the black spectrum in this wavenumber range in Figure 2) to be used for identification under the conditions of our experiment, The absorbance spectrum of propylene carbonate in Figure 2 shows that PC is best identified by the characteristic C=O stretching band at 1800 cm À 1 . These latter bands can be attributed to (bi)carbonate species, CO 3 2À , HCO 2 À , CO 3 2À and CO 3 2À respectively, as described by Figueiredo et al [17] Previous studies suggested that the existence of different vibrational bands for C=O and CÀ O bonds on bicarbonates and carbonates is due to the presence of different ion pairs of the anions with TEA + cations or solvation shells with residual water. The assignment of the different bands was done with the help of the transmission spectra and previous reports on CO 2 electrochemical reduction in acetonitrile [17] and is summarized in table 2.…”
Section: Ftir and Hplc Characterization Of Intermediates And Productsmentioning
confidence: 80%
“…Therefore, we have collected in Table 1 the corresponding electrode potentials. The assignment of the different bands was done with the help of the transmission spectra and previous reports on CO 2 electrochemical reduction in acetonitrile [17] and is summarized in table 2. The results show that PO in the acetonitrile electrolyte does not present strong IR modes that can be used for its identification, while PC clearly shows features that aid in its identification with vibrational bands at 1800, 1392, 1184, 1118 and 1053 cm À 1 .…”
Section: Ftir and Hplc Characterization Of Intermediates And Productsmentioning
confidence: 99%
“…The exsolved interfaces are expected to have enhanced catalytic activity, whereas the LSCM with oxygen nonstoichiometry may facilitate chemical CO 2 adsorption/activation at high temperatures. Figure 3A shows the chemical adsorption of CO 2 at 800°C in the in situ Fourier transform infrared (FTIR) test, which demonstrates the effective chemical adsorption/activation of CO 2 as confirmed by the transition state (TS) between the CO 2 molecule and the carbonate ion ( 19 , 20 ). With the exsolved interfaces, significant enhancement of chemical adsorption/activation of CO 2 would be anticipated on the tailored LSCM scaffold.…”
Section: Resultsmentioning
confidence: 98%